2004
DOI: 10.1007/s00701-004-0374-5
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent spinal ependymoma showing partial remission under Imatimib

Abstract: Imatimib should be considered a potential therapeutic option in recurrent ependymomas expressing PDGF receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 4 publications
0
25
1
2
Order By: Relevance
“…A variety of agents have been tried, including chronic oral etoposide, with modest success [61]. An intriguing article reported on a minor response using imatinib in a spinal ependymoma that expressed the PDGF receptors [62].…”
Section: Spinal Cord Ependymomasmentioning
confidence: 99%
“…A variety of agents have been tried, including chronic oral etoposide, with modest success [61]. An intriguing article reported on a minor response using imatinib in a spinal ependymoma that expressed the PDGF receptors [62].…”
Section: Spinal Cord Ependymomasmentioning
confidence: 99%
“…Two patients demonstrated partial responses following treatment with chronic oral etoposide, while another 5 patients maintained stable disease. Fakhrai et al 38 reported clinical improvement and mild tumor regression in a patient with a platelet-derived growth factor receptor-positive spinal ependymoma treated with imatinib. Iunes and colleagues 61 discussed a patient receiving postoperative carboplatin and radiotherapy for their intradural extramedullary tumor with multifocal presentation; the patient survived 2 years.…”
Section: Chemotherapymentioning
confidence: 99%
“…Так, N. Fakharai и соавт. [11] опубликовали кли-нический случай применения иматимаба у пациент-ки с продолженным ростом опухоли конского хво-ста (эпендимома Grade II), которая наблюдалась в течение 11 мес. Был отмечен регресс неврологиче-ской симптоматики и положительная динамика на МРТ в виде уменьшения объема опухоли.…”
Section: Discussionunclassified